Mathematical modelling of non-pharmaceutical interventions to control infectious diseases: application to COVID-19 in Kenya - Ogana, Wandera; Juma, Victor Ogesa; Bulimo, Wallace D. (Frontiers in Applied Mathematics and Statistics, 2024)
The first case of COVID-19 was reported in Kenya on 13 th March 2020 and soon after non-pharmaceutical interventions (NPIs) were established to control the spread of the disease. NPIs consisted of mitigation measures, such as wearing masks in public places, imposition of an overnight curfew, and limitation of passengers in public transport vehicles. The mitigation was followed by a period of relaxation of some of the measures, for example, by increasing the hours of operation of restaurants, reopening learning institutions, and permitting more passengers in public service vehicles. In this paper, we use a deterministic mathematical model to analyze the dynamics of COVID-19, during the baseline period of the first wave in Kenya. We simulate the system of differential equations in MATLAB and obtain values of the transmission and recovery rates that yield the basic reproduction number, ℛ 0 = 2.76, which is consistent with other published works. We also propose a mathematical model that describe NPIs and their effect on the disease transmission rates and infection levels. The model expands the scope of application to interventions that result in an increase in disease transmission rates, unlike previous models that could only handle a decrease in transmission rates. From the observed infection data, we compute the mitigation and relaxation fractions and hence deduce the impact of the interventions that were put in place. We find that mitigation measures from 9 th April to 8 th June 2020, reduced the disease transmission by 43.7% from the baseline level, while the subsequent relaxation, from 9 th June to 8 th August 2020, increased the transmission by 32% over the mitigation level. The curve of the model infection percent compares well with the observed infections.